2011
DOI: 10.1371/journal.pone.0021840
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Early Infant Diagnosis of HIV in Resource-Limited Settings: The ANRS 12140-PEDIACAM Study in Cameroon

Abstract: BackgroundEarly infant diagnosis (EID) of HIV is a key-point for the implementation of early HAART, associated with lower mortality in HIV-infected infants. We evaluated the EID process of HIV according to national recommendations, in urban areas of Cameroon.Methods/FindingsThe ANRS12140-Pediacam study is a multisite cohort in which infants born to HIV-infected mothers were included before the 8th day of life and followed. Collection of samples for HIV DNA/RNA-PCR was planned at 6 weeks together with routine v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 21 publications
5
43
2
1
Order By: Relevance
“…The median time between blood draw for DBS to result recipient by the respective health facility was 36 days (IQR: 25 -49 days). These findings are consistent with other studies from Kenya and Mozambique [8] [17] [18] but lower than study report from Cameroon and Malawi [9] [19].…”
Section: Discussionsupporting
confidence: 92%
“…The median time between blood draw for DBS to result recipient by the respective health facility was 36 days (IQR: 25 -49 days). These findings are consistent with other studies from Kenya and Mozambique [8] [17] [18] but lower than study report from Cameroon and Malawi [9] [19].…”
Section: Discussionsupporting
confidence: 92%
“…Predictors for early infant diagnosis were reported in three studies [26-28]. These showed positive associations between uptake of testing and proximity to the clinic [26], large family size [26], early HIV diagnosis of the mother [27], or having received antiretroviral prophylaxis for PMTCT [27] (webappendix Table S2). The combined estimate of the percentage of infants tested between 12 and 18 months postpartum based on 7 studies was 55.2% with 95% CI 36.4-74.1% and Prl 0.0-100.0% (Figure 4, webappendix Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…22 A larger study that included 1,587 HIV-exposed infants in Cameroon examined the association between multiple predictors and having an incomplete EID process by seven months found that women who received no prophylaxis (OR: 2.3 [95% CL: 1.2-4.1]) or short-course prophylaxis (OR: 1.4 [95% CL: 0.9-2.1]) were more likely to have an incomplete EID process compared to women who received cART. 23 …”
Section: Discussionmentioning
confidence: 99%